Scoping the characteristics and benefits of a connected double-null configuration for power exhaust in EU-DEMO. (March 2021) - Aho-Mantila, L.; Subba, F.; Coster, D.P.; Xiang, L.; Militello, F.; Lunt, T.; Moulton, D.; Reimerdes, H.; Wensing, M.; Wischmeier, M.; Ambrosino, R.; Bonnin, X.; et al.
Highlights: Divertor power exhaust in DEMO is not seen to improve in CDN without drifts. Attached regimes in DEMO CDN are associated with strong up-down asymmetries. Ar is predicted to be primarily a divertor radiator in EU-DEMO. Abstract: A double-null configuration is being considered for the EU-DEMO, due to its potential benefits for power exhaust arising from the use of two active divertors and magnetically disconnected low- and high-field sides. Using systematic parameter scans in fluid simulations, we have investigated the divertor power exhaust in the EU-DEMO in a connected double-null configuration, and compared the edge plasma properties to those obtained in a single-null configuration under detached conditions anticipated for reactor operation. Neglecting drift effects and kinetic behaviour of the neutrals, no clear benefits of the double-null configuration could yet be identified for the radiation pattern and power mitigation on open field lines. Future work should address the aforementioned physics as well as the effect of the additional X-point on core radiation.